River Ambush in Sarawak: Tanjung Batu Babi (Sungai Katibas) and Kerangan Bungkang (Sungai Ngemah) in Ngingit Issue 17 (2022) - Regina Garai, Abdullah; Neilson Ilan, Mersat (Tun Jugah Foundation, 2022)
This article is part of our fieldnote while writing a book entitled Agi Idup Agi Ngelaban published by UNIMAS in 2021. It is a written and recorded account of our observations, experiences, and reflections while conducting intermittent filedworks in various parts of Sarawak for the project. During the long hours of many intervews that we conducted, we found that the war cry Agi Idup Agi Ngelaban (As Long As I Live I Shall Fight) really inspired the frontliners in the security force, igniting an unwavering determination to defend the country tirelessly, even at the cost of their very last breath. Such fighting spirit had long been synonymous with the Sarawak Rangers. The history of Sarawak Rangers can be traced back to the formation of a security force called fortmen during the Brooke’s era. This article is based on the narratives shared to us by our key informants who served as Iban Trackers, Sarawak Rangers and even Border Scouts.